Evidence of phytoplankton blooms under Antarctic sea ice - Christopher Horvat; Kelsey Bisson; Sarah Seabrook; Antonia Cristi; Lisa C. Matthes (Frontiers in Marine Science, 2022)
Areas covered in compact sea ice were often assumed to prohibit upper-ocean photosynthesis. Yet, under-ice phytoplankton blooms (UIBs) have increasingly been observed in the Arctic, driven by anthropogenic changes to the optical properties of Arctic sea ice. Here, we show evidence that the Southern Ocean may also support widespread UIBs. We compile 77 time series of water column samples from biogeochemical Argo floats that profiled under compact (80%–100% concentration) sea ice in austral spring–summer since 2014. We find that that nearly all (88%) such measurements recorded increasing phytoplankton biomass before the seasonal retreat of sea ice. A significant fraction (26%) met a observationally determined threshold for an under-ice bloom, with an average maximum chlorophyll-a measurement of 1.13 mg/m 3 . We perform a supporting analysis of joint light, sea ice, and ocean conditions from ICESat-2 laser altimetry and climate model contributions to CMIP6, finding that from 3 to 5 million square kilometers of the compact-ice-covered Southern Ocean has sufficient conditions to support light-limited UIBs. Comparisons between the frequency of bloom observations and modeled bloom predictions invite future work into mechanisms sustaining or limiting under-ice phytoplankton blooms in the Southern Hemisphere.